Aminullah Chaudary. Political Administrators: The Story of Civil Service of Pakistan. Oxford University Press, 2011. 371 pages, Rs 895.00. (The Pakistan Development Review, 2012)
A bureaucracy is a group of individuals who are non-elected and serve as government employees to help implement rules and laws of a country. The term bureaucracy was created by combining the words ‘bureau’ which means desk or office and ‘kratos’, meaning rule or political power to govern. Different countries have adopted various ways to induct people to run the government and make new laws. Max Weber, a renowned and notable German administrative scholar is credited to be the pioneer of the use of bureaucracy in public administration. In this book on the Civil Service of Pakistan, the author has described the way bureaucratic culture gained strength and restricted the grooming of political culture in the country. He shows how ‘seniority’ overwhelmed ‘merit’ in the promotion process of the officers in the Civil Service of Pakistan (CSP), an offspring of the Indian Civil Service (ICS). The CSP officers always considered themselves as an élite class and looked down upon the politicians. The author narrates the superior attitude of Iskander Mirza (a notable member of the ICS, then CSP) in these words: “Mirza was proud of his IPS and CSP lineage and never missed an opportunity of proclaiming this fact. His admiration for the colonial system of administration was matched by a corresponding contempt for politicians.” The relationship between the bureaucracy and the military was to ensure that politicians did not make a mess of things. The bureaucracy was able to call on the military in times of crisis and never worried about its overstaying the visit. The basic theme of the Indian Civil Service was that the local Indians were recruited as officers by the British to suppress and control an enslaved people. Unfortunately, even after gaining independence the mindset of the bureaucratic staff didn’t change and they conveniently forgot that an independent nation required a different approach.